ANALISIS RASIO SOLVABILITAS UNTUK MENILAI KINERJA KEUANGAN TERHADAP ASET DAN EQUITY PADA PT SYMA BERKAH INDONESIA TAHUN 2022-2023 - Debbie Melisa Dewi; Siti Sundari (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The problem in this study is the large amount of debt borne by PT Syma Berkah Indonesia and the ability of PT Syma Berkah Indonesia to pay off the debt on assets and equity by comparing the average of the Company. The results of this study use an analysis of the financial performance of PT Syma Berkah Indonesia using solvency ratios, especially using the Debt to Equty Ratio (DER) and Debt to Asset Ratio (DAR) during 2022 and 2023. This research method uses information collection techniques and formulates answers based on facts that have been found in a problem. The research uses a descriptive quantitative research method. The source of data to conduct this research comes from PT Syma Berkah Indonesia's financial statement documents for a period of 2 years, namely 2022 and 2023. From the results of the financial statement research related to the solvency ratio analysis, it shows that in the financial statements achieved by PT Syma Berkah Indonesia with the Debt to Asset Ratio (DAR) and Debt to Equty Ratio (DER) have increased, this needs to be watched out for by the company because with the increase in the Debt to Asset Ratio (DAR) Companies must be cautious in increasing their debt and carefully manage their debt as efficiently as possible to reduce future financial risks and maintain even better financial performance. Meanwhile, the increase in the Debt to Equty Ratio (DER) shows that the company relies on debt to finance its operations and investments, so that the financial risks experienced by PT Syma Berkah Indonesia are also increasing. The condition of PT Syma Berkah Indonesia's financial performance from the perspective of Debt to Equity Ratio (DER) needs to be careful, because the company's debt in 2023 has increased very significantly. With this research, it is hoped that it can help financial management in measuring the extent to which companies can pay off their obligations both in the short and long term. And in the future can make wise and appropriate decisions.